Novel Oxime-Derivatized Synthetic Triterpene Glycosides as Potent Saponin Vaccine Adjuvants - Fuentes, Roberto; Aguinagalde, Leire; Pifferi, Carlo; Plata, Adrián; Sacristán, Nagore; Castellana, Donatello; Anguita, Juan; Fernández-Tejada, Alberto (Frontiers in Immunology, 2022)
Vaccine adjuvants are key for optimal vaccine efficacy, increasing the immunogenicity of the antigen and potentiating the immune response. Saponin adjuvants such as the carbohydrate-based QS-21 natural product are among the most promising candidates in vaccine formulations, but suffer from inherent drawbacks that have hampered their use and approval as stand-alone adjuvants. Despite the recent development of synthetic derivatives with improved properties, their full potential has not yet been reached, allowing the prospect of discovering further optimized saponin variants with higher potency. Herein, we have designed, chemically synthesized, and immunologically evaluated novel oxime-derivatized saponin adjuvants with targeted structural modifications at key triterpene functionalities. The resulting analogues have revealed important findings into saponin structure-activity relationships and have shown superior adjuvant activity in terms of significantly increased antibody response augmentation compared to our previous saponin leads. These newly identified saponin oximes emerge as highly promising synthetic adjuvants for further preclinical development towards potential next generation immunotherapeutics for future vaccine applications.